Chiesa italiana e migrazioni nel periodo post-conciliare = The Italian Church and human mobility since the Second Vatican Council - Garau, Eva (Rivista di storia della Chiesa in Italia, 2019)
Since the mid-1960s, the Church and the Holy See responded to the pressure of globalisation and the rise in number of migrants by reflecting on the transformation of Western societies and the issue of Christians emigrating in search of better living conditions. This article analyses documents and outputs produced by the Italian national conference of bishops (CEI) since its creation, in order to assess the role it played and still plays in the national debate on migration, as well as in the growing awareness of Italy’s transformation from a country of many diasporas to the final destination of migratory movements. Moreover, it looks at the language of human rights employed by Italian bishops and their attempt to contextualise human mobility in the framework of urban and social transformation, which marked the last century of Italian history.